2022
DOI: 10.1039/d1ra08385f
|View full text |Cite
|
Sign up to set email alerts
|

Nano-molecularly imprinted polymers (nanoMIPs) as a novel approach to targeted drug delivery in nanomedicine

Abstract: The review highlights the recent advances in fabrication of molecularly imprinted polymers and their applicability for drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 88 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…33,34 MIPs have been extensively researched for use as drug delivery systems for this exact reason, and many notable reviews are available within current literature. [35][36][37] Due to the breadth of applications for MIPs, functional monomer(s) and crosslinker(s) for use in MIP preparation are chosen with properties (charge, size, chemical identity) of the template in mind. Commonly used functional monomers and crosslinkers utilized in MIP synthesis can be found in Fig.…”
Section: Molecular Designmentioning
confidence: 99%
“…33,34 MIPs have been extensively researched for use as drug delivery systems for this exact reason, and many notable reviews are available within current literature. [35][36][37] Due to the breadth of applications for MIPs, functional monomer(s) and crosslinker(s) for use in MIP preparation are chosen with properties (charge, size, chemical identity) of the template in mind. Commonly used functional monomers and crosslinkers utilized in MIP synthesis can be found in Fig.…”
Section: Molecular Designmentioning
confidence: 99%
“…It has been observed that biologically degradable cross-linking polymers are among the most promising materials in targeted and regulated drug delivery . Few papers are encountered in the literature regarding biodegradable molecularly imprinted polymers possessing magnetic characteristics and their applications in targeted drug delivery. …”
Section: Introductionmentioning
confidence: 99%
“…13 This technique is based on a phenomenon of molecular imprinting 14,15 that has already earned its place in the biomedical research as an effective tool for diagnostics and imaging. [16][17][18] The method involves a formation of nano-molecularly imprinted polymers (nanoMIPs) on the surface of cells by selfassembly of monomers possessing complementary functional groups around the side chains of exposed peptides or "epitopes" followed by polymerisation. The surface peptides capable forming the complexes with nanoparticles are protected against digestion therefore can be eluted from the nanoparticles and then sequenced using standard LC-MS/MS protocols (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…13 This technique is based on a phenomenon of molecular imprinting 14,15 that has already earned its place in the biomedical research as an effective tool for diagnostics and imaging. 16–18…”
Section: Introductionmentioning
confidence: 99%